2014
DOI: 10.1021/nl4047784
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Capacitive Behaviors of Graphene Oxide Based Solid-State Supercapacitors

Abstract: Substantial differences in charge storage mechanisms exist between dielectric capacitors (DCs) and electrochemical capacitors (ECs), resulting in orders of magnitude difference of stored charge density in them. However, if ionic diffusion, the major charge transport mechanism in ECs, is confined within nanoscale dimensions, the Helmholtz layers and diffusion layers will overlap, resulting in dismissible ionic diffusion. An interesting contradiction between appreciable energy density and unrecognizable ionic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 32 publications
2
70
0
Order By: Relevance
“…Some studies have been devoted to the development of inorganic solid-state electrolytes for ESs, 324,325,419 although they receive much less attention when compared to the polymer-based solid-state electrolytes. 419,420 Interestingly, Zhang et al 419 studied an all-solid-state sandwiched RGO//GO//RGO supercapacitor with a layering structure. However, they are generally mechanically robust and thermally stable.…”
Section: Solid-or Quasi-solid-state Electrolytes For Essmentioning
confidence: 99%
“…Some studies have been devoted to the development of inorganic solid-state electrolytes for ESs, 324,325,419 although they receive much less attention when compared to the polymer-based solid-state electrolytes. 419,420 Interestingly, Zhang et al 419 studied an all-solid-state sandwiched RGO//GO//RGO supercapacitor with a layering structure. However, they are generally mechanically robust and thermally stable.…”
Section: Solid-or Quasi-solid-state Electrolytes For Essmentioning
confidence: 99%
“…Although graphene oxide usually works as the precursor of RGO in the development of graphene‐based MSC, the hydrated GO can be a part of electrolyte or membrane as reported previously …”
Section: Graphene‐based Materials In Planar Interdigitated Microsupercmentioning
confidence: 99%
“…The relative permittivity of the samples can be deduced from the capacitance of the bulk [26] using equation (2):…”
Section: Resultsmentioning
confidence: 99%
“…Large values of relative dielectric permittivity are also suggested from characterizations of composite materials in which a small fraction of GO added to a polymer enhances the effective permittivity of the composite [16][17][18][19][20][21][22]. By contrast, other studies have reported more moderate values of permittivity, of about 3, or less, in frequency ranges typically from 100 to 1000 Hz [23][24][25][26]. Uses of GO as dielectrics in transistors led also to the conclusion that GO has a relative permittivity typically between 3 and 5 [27][28][29].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation